10 rules of success - "Agarwal, Mridula" (New Delhi, 2006)
The 10 Rules of Success, as it has been named, deals with the laws of attaining success in life. Time tested truths have been put in a set of ten to be strictly followed rules. Written with an in depth understanding of various laws of success along with psychological aspects of human mind, its perceptions, understandings, limitations and strengths, it not only illustrates the problem but also gives suggestions for overcoming them with ease.
Keywords: Success